Analysis of Seventh-Grade Students' Fundamental Mathematical Conceptual Understanding in Social Arithmetic - Fitri Fitri; Chairuddin Chairuddin; Achmad Salido; Marniati Marniati (Global Journal of Mathematics Education, 2026)
This study investigated the characteristics of seventh-grade students’ mathematical conceptual understanding of Social Arithmetic and identified the factors influencing that understanding. The study employed a qualitative descriptive approach involving 18 seventh-grade students from SMPN 6 Watubangga. Three students were subsequently selected as key informants through purposive sampling based on variations in their problem-solving strategies, conceptual understanding, and communication abilities. Data were collected through problem-solving tasks and structured interviews and were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification. The findings revealed that students demonstrated varying levels of mathematical conceptual understanding, which were generally characterized by partial mastery of concepts and difficulties in applying concepts consistently across different problem situations. While some students were able to identify relevant information and recognize fundamental concepts such as percentages and discounts, they frequently encountered computational errors and difficulties in communicating mathematical reasoning. Other students struggled to connect multiple Social Arithmetic concepts, determine appropriate solution strategies, and solve contextual problems requiring multistep reasoning. The factors influencing students’ conceptual understanding included limited mastery of fundamental concepts, difficulties in connecting related concepts, insufficient procedural accuracy, and limited mathematical communication skills.